Determination and monitoring of vegetation stress using hyperspectral remote sensing - Sani, Yahaya (2013)
Stress causes crops to grow below their potential and this affects the vitality and physiological functioning of the plants at all levels leading to reduction in yield. Remote sensing of vegetation is regarded as a valuable tool for the detection and discrimination of stress, especially over large or sensitive regions.